Using innovation to hedge against economic and political uncertainty evidence from emerging nations - Rajeev K. Goel; Michael A. Nelson (Kiel Institute for the World Economy (IfW), 2019)
Using data on 135 countries, this paper studies the determinants of process innovation introduction, focusing on the impacts of economic and political uncertainties. Greater uncertainty, on the one hand, can lower potential benefits from innovation introductions, while on the other hand, the introduction of innovations might enable firms to hedge against uncertainty. The empirical literature has mostly considered uncertainty-investment nexus, and this study uniquely considers uncertainty-innovation introductions. Employing two different measures of economic and political uncertainty across different time lags, results are consistent with the hedging story - greater economic and political uncertainties induce firms to introduce process innovations to the market. With regard to firms' attributes, sole proprietorships and R&D-performing firms were more likely to introduce innovations, while firms located in island nations were less likely to do so. Firms' size and vintage did not have an appreciable influence on the incentives to introduce innovations. Some policy implications of these findings are discussed.
Keywords: O33; O31; O57; L29; 330; economic uncertainty; political uncertainty; stability; innovation; hedging; R&D; sole proprietorship; inflation; state fragility